Comparison of Oviposition and Adult Trapping to Monitor wMel Introgression for Wolbachia-Based Vector Control - Elisabeth Nelson; Thiago N. Pereira; Erica Milena de Castro Ribeiro; Bianca Daoud Mafra e Silva; Carolina Camillo; Thiago Rodrigues da Costa; Mauro M. Teixeira; Albert I. Ko; Derek A. T. Cummings; Luciano A. Moreira (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Wolbachia introgression into Aedes aegypti ( Ae. aegypti ) mosquito populations is an effective strategy for preventing dengue and is currently under evaluation for WHO prequalification. The standard protocol for trials and deployments currently being conducted in Brazil by the World Mosquito Program (WMP) for long-term monitoring of Wolbachia introgression involves the use of BG-Sentinel traps (BG-traps; Biogents AG [Regensburg, Germany]), which are labor-intensive and costly. More affordable alternatives, such as oviposition traps (ovitraps), have been used in other settings; however, a comparison of the WMP protocol for Wolbachia surveillance has not been performed. As part of the EVITA dengue trial, Ae. aegypti eggs and adults were collected from 124 ovitraps and 237 BG-traps across 12 clusters in Belo Horizonte, Brazil, between March and May 2023. Eggs collected from ovitraps were reared to L3 and L4 larvae, and w Mel Wolbachia was detected using quantitative polymerase chain reaction testing in larvae and adult mosquitoes from BG-traps. Mixed-effects models were used to compare cluster-level estimates of w Mel introgression derived from ovitrap and BG-trap data over time. Among 3,675 larvae reared from ovitraps, w Mel prevalence was 0.50 (95% CI: 0.48–0.51), whereas 1,244 adults from BG-traps had a prevalence of 0.45 (95% CI: 0.42–0.48). Cluster-level introgression estimates from larvae and adults were strongly correlated (Spearman’s r = 0.70; P